Nutritional status of school going children and adolescents aged 9-13 years at Haldia in West Bengal, India - Sudip Datta Banik; Soumita Chatterjee (Indonesian Pediatric Society Publishing House, 2010)
Background Malnutrition in children and adolescents is a global problem. In developing nations of Africa and Southeast Asia, the prevalence of undernutrition in children is very high. There is scanty data 'With respect to the nutritional status of school going children and adolescents, especially from sub􀁉urban and rural areas in India. Objective A study was undertaken among boys (n = 174) and girls (n = 128) aged 9􀁉 13 years in a sub􀁉urban area of Purba Medinipur district of West Bengal in India to understand age and sex variation of nutritional status of the subjects. Methods A cross􀁉sectional study among the school􀁉going children and adolescent aged 9􀁉 13 years was done during June􀁉September 2009 in Haldia. Results Age and sex variation of anthropometric characteristics (body mass index or BMI and conicity index or CI) revealed that remarkable sections of both the sexes were suffering from underweight (8.30%), stunting (14.60%) and wasting (2.80%). Significant sex differences were observed in cases of mean CI (P=O.OO1), weight􀁉for􀁉age z􀁉score (P = 0.0001) and weight-for-height ,-score (P 􀀂 0.0001). Discussion Besides notable prevalence of under nutrition in both sexes, situation of the girls is worse (underweight - 11.70% and stunting - 21.10%) compared to the boys. This is most evident among the subjects of both sexes aged 11 and 12 years.